Impaired sensitivity to thyroid hormones is associated with hyperuricemia in a Chinese euthyroid population - Lu, Yingning; Wang, Jie; An, Yu; Liu, Jia; Wang, Ying; Wang, Guang; Leng, Song (Frontiers in Endocrinology, 2023)
Abstract Objective: Impaired sensitivity to thyroid hormones has been reported a common metabolic disorder and it remains poorly understood whether it interplays with uric acid (UA) metabolism as an established risk factor for cardiovascular diseases (CVD).We aimed to investigate the relationship between thyroid hormone sensitivity and elevated UA in Chinese euthyroid population. Methods: Totally, 15955 euthyroid subjects were included in this study. Thyroid hormone sensitivity indices were calculated, including thyroid feedback quantile-based index (TFQI), Chinese-referenced parametric TFQI (PTFQI), TSH index (TSHI) and thyrotropin thyroxine resistance index (TT4RI), and FT3/FT4 ratio. Liner and logistic regression analyses were performed to detect the association between thyroid hormone sensitivity and elevated UA . Results: Subjects with reduced sensitivity to thyroid hormones had increased UA levels in both genders (P for trend < 0.001). Logistic and liner regression analyses showed that higher TFQI, PTFQI, TSHI, and TT4RI were positively associated with elevated UA levels, whereas a negative association of FT3/FT4 ratio. The odds ratio (OR) of the highest versus the first quartile of TFQI was 1.20 (1.05, 1.38) in men and 1.80 (1.46, 2.23) in women (P < 0.001). PTHQI, TSHI, and TT4RI obtained similar results in both genders. Conversely, the highest quartile of FT3/FT4 ratio was negatively correlated with elevated UA levels [males: OR 0.78 (0.68,0.89), females: OR 0.66 (0.53,0.81)]. Conclusion: Impaired sensitivity to thyroid hormones was associated with elevated UA levels in euthyroid subjects. Our findings shed light on role of thyroid hormone sensitivity in UA metabolism.